TRANSFORMASI E-GOVERNMENT DALAM PERSETUJUAN BANGUNAN GEDUNG:: Melalui Sistem Informasi manajemen Bangunan Gedung (SIMBG) di Kota Kendari Sulawesi Tenggara - Aminudin; Suryani BB; Makmur Kambolong; Suci Nurzakinah (Halu Oleo University, 2024)
The aim of this research is to determine the application of e-government in building approval services through SIMBG at the Kendari City Investment and One-Stop Integrated Services Service. Researchers used descriptive qualitative research methods. There were 9 informants in this study who were determined using purposive sampling techniques. Data collection techniques through in-depth interviews and documentation studies. Building Approval Services through SIMBG at the Kendari City One-Stop Integrated Services and Investment Service can be seen from: 1) Physical evidence of the availability of good and adequate public service locations. 2) The Reliability Dimension (reliability) of the Kendari City one-stop capital investment and service department is still not in accordance with applicable regulations and SOPs. 3) Responsiveness, which is still not good, can be seen from the lack of response by employees to complaints or complaints from the public in services related to the PBG permit application process through SIMBG. 4) The insurance dimension is good, as seen from the existence of several guarantees, namely data and document security guarantees, PBG document authenticity guarantees and service guarantees. 5) Empathy, this can be seen from the lack of professionalism of employees towards applicants regarding PBG services through SIMBG.